Perlindungan Hukum Pekerja Rumah Tangga Dalam Undang- Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Muzakkir (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2023)
One of the principles in the State of Law, the protection of human rights. Everyone needs work to meet the needs of their lives to be more prosperous, work is a demand that must be met by everyone in maintaining their lives. To date, there is no specific legal umbrella in providing protection for domestic workers. Legal protection for domestic workers can only be implemented if there is a clear legal basis to apply to domestic workers and make them workers in the juridical sense. This article is classified as literature research with a qualitative approach. The methodology used is the study of normative legal studies. The results of the study concluded that the purpose of legal protection as stated in Article 4 of Law Number 13 of 2003 concerning Manpower is to provide protection to workers in realizing welfare and improving the welfare of workers and their families. Legal certainty is a judicial protection against arbitrary actions which means that a person will be able to obtain something expected under certain circumstances.